2010
DOI: 10.2478/v10131-0009-6
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Osteoporosis among Underweight and Obese Sedentary Young Women

Abstract: The purpose of the present study was to examine the effect of a walking program on bone mass density (BMD) among healthy obese and thin young girls. Twenty untrained obese (n=10) and thin (n=10) girls, 20-25 years, volun teered to participate in this study. Before and after the training program both groups had an anthropometric measurement, a blood analysis and a BMD evaluation. Each walking session consisted of 30 minutes walking between 50-75% of maximal heart rate, 3 days per week for 2 months. After the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
1
1
Order By: Relevance
“…Results of this research were inconsistent with a study by Habib-Zadeh et al (2010) in which significant effects on bone mineral density was observed on obese and thin girls [4]. Possible causes of this inconsistency can be the shorter duration (two months), low-intensity workouts (walking with a heart rate of 50% to 75%) or lower age and weight of subjects compared to the current study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Results of this research were inconsistent with a study by Habib-Zadeh et al (2010) in which significant effects on bone mineral density was observed on obese and thin girls [4]. Possible causes of this inconsistency can be the shorter duration (two months), low-intensity workouts (walking with a heart rate of 50% to 75%) or lower age and weight of subjects compared to the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…However, one effective, low-cost and non-pharmacological approach to achieve this goal is physical activity, which is the most important environmental factor modulator to increase or maintain bone mineral density in adults and children [3]. Habib-Zadeh et al (2010) investigated the effect of walking on BMD (hip and lumbar vertebrae) of 40 obese and thin non-athlete girls and did not observe a significant effect on hip and waist BMD of the subjects [4].…”
Section: Introductionmentioning
confidence: 99%